Вплив ступеню однорідності вугільної шихти та міцність коксу - Шмельцер, Катерина Олегівна; Кормер, Марина Віталіївна; Мірошниченко, Денис Вікторович; Дигас, Наталія Валеріївна (Національний технічний університет "Харківський політехнічний інститут", 2023)
Встановлено, що підвищення гомогенності шихти обумовлює збільшення механічної міцності коксу за показником дробимості М25 на 2-4%, при цьому стиранність за М10 зменшується на 0,5%. Рекомендовано здійснювати організоване змішування вугільної шихти за допомогою змішувальних машин.

It was established that the increase in the homogeneity of the batch leads to an increase in the mechanical strength of coke according to the M25 crushability index by 2-4%, while the abrasion resistance according to M10 decreases by 0.5%. It is recommended to carryout organized mixing of the coal batch with the help of mixing machines.
Influence the degree of homogeneity coal batchon coke strength
Keywords: організоване змішування; однорідність технологічних властивостей; багатобасейнова сировинна база; organized mixing; homogeneity of the technological properties; multi-basin coking raw material base